Landscape cover type, not social dominance, is associated with the winter movement patterns of Snowy Owls in temperate areas. Issue 2 (5th March 2021) - McCabe, Rebecca A; Therrien, Jean-François; Wiebe, Karen L; Gauthier, Gilles; Brinker, David; Weidensaul, Scott; Elliott, Kyle
Abstract: Migrating animals occur along a continuum from species that spend the nonbreeding season at a fixed location to species that are nomadic during the nonbreeding season, essentially continuously moving. Such variation is likely driven by the economics of territoriality or heterogeneity in the environment. The Snowy Owl ( Bubo scandiacus ) is known for its complex seasonal movements, and thus an excellent model to test these ideas, as many individuals travel unpredictably along irregular routes during both the breeding and nonbreeding seasons. Two possible explanations for this large variation in the propensity to move are (1) dominance hierarchies in which dominant individuals (adult females in this case) monopolize some key, consistent resources, and move less than subdominants; and (2) habitat heterogeneity in which individuals foraging in rich and less heterogenic environments are less mobile. We analyzed fine-scale telemetry data (global positioning system [GPS]/global system for mobile communication [GSM]) from 50 Snowy Owls tagged in eastern and central North America from 2013 to 2019, comparing space use during the winter period according to sex and age, and to land cover attributes. We used variograms to classify individuals as nomadic (58%) or range-resident (42%), and found that nomadic owls had ten times larger wintering areas than range-resident owls. The frequency of nomadism was similar in socially-dominant adult females, immatures, and males. However, nomadism increased from west to east, and north to south, and was positively associated with the use of water and negatively associated with croplands. We conclude that many individual Snowy Owls in Eastern North America are nomadic during the nonbreeding season and that movement patterns during this time are driven primarily by extrinsic factors, specifically heterogeneity in habitat and prey availability, as opposed to intrinsic factors associated with spacing behavior, such as age and sex. Graphical Abstract: Lay Summary: Global positioning system (GPS)/Global system for mobile communication (GSM) transmitters were used to document two movement behaviors, range-residency, and nomadism in wintering Snowy Owls. Social dominance plays little role in determining the distribution of wintering owls in temperate areas. Mobility increased west to east, and north to south, and was more common along with bodies of water than in croplands.